ICT Concepts Development in Educational Theory and Practice since the Time of Independence of Ukraine - Chasnikova Olena Volodymyrivna; Dubrovina Iryna Volodymyrivna; Zinchenko Olha Mykolayivna (International Journal of Science Annals, 2020)
Background and Aim of Study: The article deals with ICT concepts in the educational theory and practice of Ukraine. It is noted that scientists are exploring different aspects such as a concept, a strategy for implementing the concept, real experience, etc. The analysis of ICT concepts in education which were created during the independence period, has highlighted a number of contradictions that accompany this process. The aim of the study: to consider ICT concepts which were created in the system of education in Ukraine during the independence period. Material and Methods: In the study, the following general scientific methods were used: analysis (historical and pedagogical), synthesis, comparison, generalization. Results: ICT concepts implemented in Ukraine’s education, not only attest to the emergence of innovative information and technological realities in the field of science and education, but also are considered to be new realities, and therefore need to be researched by scholars of different branches – philosophers, educators, sociologists, psychologists, etc. – both in terms of methodology and trends of changes in the reference field of educational informatization. Conclusions: ICT concepts in Ukraine’s education, created during the independence period, reflect the course of a controversial process of a state formation. Being innovative by design, concepts, laws, strategies, programs, etc. have been based on traditional, or even outdated, principles of state development. A legislative approval of the National Program of Informatization and periodic changes in innovative nature of its content in relation to ICT in education, showed progressive trends of conceptual importance.